Improving Nutrition Care for Nursing Home Residents Using the INRx Process - Crogan, Neva L. (2006)
The purpose of this article is to describe the Individual Nutrition Rx (INRx) assessment process and report findings on elder nutritional status, common nutrition problems identified by the INRx process, resolution outcomes from each problem, and the most efficacious approaches used to address the identified nutrition problems. The study used a two-group prospective quasi-experimental design with measures taken at baseline and at 6 months. Participants in the treatment group (n = 41) received the 6-month INRx assessment process, while residents in the comparison group (n = 40) received routine care specific to their nursing home. The most frequent nutritional problems identified were appetite change, poor positioning while eating, and problems with oral status. A total of 39 approaches were recommended by the interdisciplinary research team. Serum albumin and prealbumin, and depression scores were all significantly improved post intervention. The problems, approaches, and outcomes identified during the INRx process support the premise that interdisciplinary teams following the INRx process can assess complex nutritional problems and influence outcomes for older adults living in nursing homes.